Software technologies : 14th International Conference, ICSOFT 2019, Prague, Czech Republic, July 26-28, 2019, Revised selected papers /: 14th International Conference, ICSOFT 2019, Prague, Czech Republic, July 26-28, 2019, Revised selected papers. (2020) - Unknown
No abstract available